Keberlakuan Non-Refoulement Principle Dikaitkan Dengan Sovereignty Principle: Tinjauan Terhadap Pengungsi Rohingya di Indonesia - Wuri Sumampouw; Kana Kurnia; Nur Arfiani; Reza Hadrian (Jurnal USM Law Review)
This research aims to determine the determination of the status of the Rohingya ethnic group according to the Refugee Convention and the application of the principle of non-refoulement in handling Rohingya refugees in Indonesia in relation to the principle of sovereignty, and then whether the application of the principle of non-refoulement is absolute or not applied in Indonesia. Due to the large number of Rohingya ethnic groups entering Indonesian territory and causing social problems, security can even threaten sovereignty. The research method is normative legal research, relying on secondary data. The research results show that Indonesia is not a country that has ratified the 1951 convention, as a result, it is difficult for asylum seekers to obtain protection regarding their certainty, and considering the ongoing security situation in Myanmar, of course, the only hope for asylum seekers to achieve a long-term solution is through resettlement in third countries and even though Indonesia has not ratified the 1951 convention, Indonesia still needs to comply with the principle of non-refoulement even though there are no penalties imposed on Indonesia if Indonesia violates the 1951 convention and forces refugees to leave Indonesia considering that the convention does not explain in writing what The consequences that non-convention countries will face if they reject asylum seekers and refugees and force them to leave Indonesia.